MEDIASI DALAM PENYELESAIAN PERKARA PIDANA DI INDONESIA - Natakharisma, Keyzha; Suantra, I Nengah (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 05, November 2013)
Mediation is generally known as a form of Alternative Dispute Resolution in the civil law, but in the development of mediation in criminal cases can be made known to the Penal Mediation. Penal mediation can be used in some special category of criminal acts. Application of mediation in the settlement of the criminal case does not extend a purpose other than the conflict between the offender and the victim but to help law enforcement agencies in reducing the accumulation of case files. The purpose of this paper is to understand and know about how a mediation mechanism can be used to solve a criminal case in Indonesia. In this study, using descriptive normative method. Normative approach to the legal research using secondary data sources, while the descriptive approach is the method of research that seeks to describe and interpret objects in accordance with what it is.
Keywords: Restorative Justice, Mediation Penal